PENGARUH FREE CASH FLOW, GROWTH, INVESTMENT OPPORTUNITIES, LIFE CYCLE STAGE TERHADAP DIVIDEND POLICY PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - B31112159, SUSANTI M (Jurnal Manajemen Update, 2016)
The purpose of this study is to find the effect of independent variables are Free Cash Flow, Growth, Investment Opportunity and Life Cycle Stage to the dependent variable is Dividend Policy. The research data were obtained from the annual reports of publicly traded companies listed on the Indonesia Stock Exchange (IDX) with a sample of 25 companies listed on characteristics specific sampling for the period 2010 to 2013. The analysis method used analysis multiple regression. The results of this study indicate that the variable Free Cash Flow, Growth, and Life Cycle Stage affect positively and significantly to the Dividend Policy, while the variable Investment Opportunity no significant effect on dividend payout policy and the variables that affect most to the Dividend Policy is variable Free Cash Flow. These results prove that the increase in free cash flow in the company, the high asset growth and conditions maturity life cycle of the company will increase the dividend payout policy.Â  Keywords : dividend, free cash flow, growth, investment opportunities, life cycle stage